The Validity of a PBL-Based E-Worksheet Chemical Equilibrium for Enhance Creative Thinking - Abidin, Muhammad Syahrul; Novita, Dian (Pendidikan Kimia FKIP Universitas Jambi, 2025)
This study aims to determine the validity of the Electronic Student Worksheet (E-LKPD) based on the PBL (Problem Based Learning) model to improve students' creative thinking skills in chemical equilibrium materials. The development model in this study is ADDIE (Analyze, Design, Development, Implementation, & Evaluation), and is limited to the development stage and there is an evaluation at each stage. The validation results are analyzed based on the mode in each aspect. Based on the validation results, a mode score of 3 is obtained for each aspect of content validity and construct validity with a valid category. So that the PBL-based E-LKPD that is developed can be considered valid to improve students' creative thinking skills Keywords: Electronic Student Worksheets, Creative Thinking Skills, Problem Based Learning, Chemical Equilibrium